SOMM: Industry Oriented Ontology Management Tool - Horrocks, I; Cuenca Grau, B; Kharlamov, E; Jimenez Ruiz, E; Nenov, Y; Lamparter, S; Mehdi, G; Ringsquandl, M; Brandt, S (Springer Verlag, 2016)
This paper describes the outcomes of an ongoing collaboration between Siemens and the University of Oxford, with the goal of facilitating the design of ontologies and their deployment in applications. Ontologies are mainly used in Siemens to capture the conceptual information models underpinning a wide range of applications. We start by describing the key role that such models play in two use cases in the manufacturing and energy production sectors. Then, we discuss the formalisation of information models using ontologies, and the relevant reasoning services. Finally, we present SOMM—a tool that supports engineers with little background on semantic technologies in the creation of ontology-based models and in populating them with data. SOMM implements a fragment of OWL 2 RL extended with a form of integrity constraints for data validation, and it comes with support for schema and data reasoning, as well as for model integration. Our evaluation demonstrates the adequacy of SOMM’s functionality and performance for Siemens applications.